2018
DOI: 10.1038/s41598-018-20743-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation by Trichodesmium and unicellular diazotrophs in the northern South China Sea and the Kuroshio in summer

Abstract: Distribution of diazotrophs and their nitrogen fixation activity were investigated in the northern South China Sea (nSCS) and the Kuroshio from July 16th to September 1st, 2009. N2 fixation activities in whole seawater and <10 μm fraction at the surface were measured by acetylene reduction assay. Higher activities were observed at the East China Sea (ECS) Kuroshio and the nSCS shelf. The nSCS basin showed a low N2 fixation activity. The <10 μm fractions (unicellular diazotrophs) contributed major portion to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 65 publications
2
41
2
3
Order By: Relevance
“…These results suggested that filamentous diazotrophs contribute significantly to biological N 2 fixation in the ECS, particularly in the Kuroshio mainstream and bifurcation region. However, their new N input and contribution to N 2 fixation in Kuroshio and the offshore ECS might underestimate previously (Chang et al, 2000;Jiang et al, 2018;Shiozaki, Takeda, et al, 2015;Wu et al, 2018;Zhang et al, 2012), because of scare measured data in Kuroshio. Therefore, contributions of filamentous cyanobacteria and unicellular diazotrophs to N 2 fixation in the ECS remain unclear, and direct measurement of size-fractioned N 2 fixation is required.…”
Section: Estimation Of N 2 Fixation By Filamentous Diazotrophs Duringmentioning
confidence: 93%
See 2 more Smart Citations
“…These results suggested that filamentous diazotrophs contribute significantly to biological N 2 fixation in the ECS, particularly in the Kuroshio mainstream and bifurcation region. However, their new N input and contribution to N 2 fixation in Kuroshio and the offshore ECS might underestimate previously (Chang et al, 2000;Jiang et al, 2018;Shiozaki, Takeda, et al, 2015;Wu et al, 2018;Zhang et al, 2012), because of scare measured data in Kuroshio. Therefore, contributions of filamentous cyanobacteria and unicellular diazotrophs to N 2 fixation in the ECS remain unclear, and direct measurement of size-fractioned N 2 fixation is required.…”
Section: Estimation Of N 2 Fixation By Filamentous Diazotrophs Duringmentioning
confidence: 93%
“…Like buoyant Trichodesmium , diatom–diazotroph associations (DDAs) have an important role in carbon sequestration and in the biological pump because of their heavy, silicon‐containing cell walls (Brzezinski et al, ; Karl et al, ; Subramaniam et al, ; White et al, ). Under the drastic increase in p CO 2 and sea surface temperature (SST), the distribution, controlling factors, and N 2 fixation of Trichodesmium and Richelia / Calothrix are receiving greater interest (Sohm, Webb, & Capone, ; Subramaniam et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent result obtained from a global survey of genes used for the assimilation of the organic compounds in picocyanobacteria directly indicated that the Synechococcus clade-II prefer to take up amino acids and NH 4 for use in biogenesis (Yelton et al 2016). During the study period in 2009, besides excretion of zooplankton, the diazotrophic cyanobacteria, Trichodesmium, usually thriving in the Kuroshio Current in summer, might provide considerable amount of NH 4 , (Chen et al 2008;Chung et al 2012;Wu et al 2018). Additionally, the study area is an excellent fishing ground, and the contribution of fish excrement to the organic nitrogen inventory cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Trichodesmium is highly abundant in the Kuroshio Current (35,36), which directly flows through the KST area. Before the extreme events, cyanobacterial production in the KST area was suppressed by the high concentration of toxic metals such as arsenic, cadmium, copper and lead (37).…”
Section: Dietary Response To the Drastic Biogeochemical Changes And Hmentioning
confidence: 99%